The contracted forms in the Present Indicative Middle and Passive of Athematic Verbs in Poetry of Ancient Greece of Archaic and Classical Period - Frąckiewicz, Katarzyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2015)
The aim of the paper is an attempt at analysing the contracted forms of the second-person singular of athematic verbs in Greek poetry. Verbs such as dÚnamai and ™p…stamai have forms with -sai and -hi, -ai in the present indicative middle and passive. Contemporary scholars express different views on where the contracted forms appear. The paper presents the opinions of ancient grammarians and modern linguists on the mentioned subject. The critical analysis of these opinions has been contrasted with the forms present in the poetry of archaic and classical period.